ASPEK AFEKTIF TAKSONOMI BLOOM PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VI SEKOLAH DASAR SE KECAMATAN ALIAN - Sari, Nurty Gofita (EKUIVALEN - Pendidikan Matematika, 2013)
This study aimed to understand determine 1. affective aspects of students' attitudes of Bloom's taxonomy the learning mathematics in Grade VI Elementary School District Alian 2. Student interest of effective aspect Bloom?s taxonomy the learning mathematics in Grade VI Elementary School District Alian. This research is a qualitative descriptive. Participants who this study were 15 students in public elementary school District Alian. The sampling technique used purposive sampling and snowball sampling. Collecting data using the interview. Researchers look is like data validation. The result show that: 1. VI grade elementary school students have a positive attitude to mathematics; 2. student interest of affective aspects Bloom's taxonomy does not show an interest in of teaching mathematics. Key words : affective aspects of Bloom's taxonomy, interest, and attitude